Endhorpin Massage on The Process of Uterine Involution in Postpartum Women - Ni Made Ari Febriyanti; Ni Nyoman Deni Witari; Ni Ketut Ayu Sugiartini (Jurnal MID-Z (MIDWIFERI ZIGOT), 2023)
During the postpartum period, physiological changes occur in the body, one of which is the reproductive system, namely the process of uterine involution. The process of this change can sometimes cause complications, which will cause bleeding and death of the mother. One of the efforts to prevent post partum bleeding is by stimulating the process of uterine involution, one of which is endorphin massage. Endhorpine massage is a light touch on the neck, arms and hands that can stimulate the secretion of endorphins to provide a relaxing and comfortable effect on the body through the skin surface and stimulate the release of the hormone oxytocin which can stimulate uterine contractions, thereby accelerating the process of uterine involution. The purpose of this study was to determine the effect of Endhorpine Massage on the Process of Uterine Involution in Postpartum Mothers.  The sampling technique of this research is purposive sampling. The independent variable in this study was endhorpine massage and the dependent variable was the process of uterine involution. Data were collected using an observation sheet for the height of the uterine fundus, and SOP for endhorpin massage for endhorpin massage and data analysis was carried out in stages including univariate and bivariate (Wilcoxon). BMidwifes can provide counseling and training on endorphins massage to speed up the process of uterine involution.